Macrophage-infectivity potentiator of Trypanosoma cruzi (TcMIP) is a new pro-type 1 immuno-stimulating protein for neonatal human cells and vaccines in mice - Radwanska, Magdalena; de Lemos Esteves, Frédéric; Linsen, Loes; Coltel, Nicolas; Cencig, Sabrina; Widart, Joelle; Massart, Anne-Cécile; Colson, Séverine; Di Paolo, Alexandre; Percier, Pauline; Ait Djebbara, Sarra; Guillonneau, François; et al. (Frontiers in Immunology, 2023)
This work identifies the protein “macrophage infectivity potentiator” of Trypanosoma cruzi trypomastigotes, as supporting a new property, namely a pro-type 1 immunostimulatory activity on neonatal cells. In its recombinant form (rTcMIP), this protein triggers the secretion of the chemokines CCL2 and CCL3 by human umbilical cord blood cells from healthy newborns, after 24h in vitro culture. Further stimulation for 72h results in secretion of IFN-γ, provided cultures are supplemented with IL-2 and IL-18. rTcMIP activity is totally abolished by protease treatment and is not associated with its peptidyl-prolyl cis-trans isomerase enzymatic activity. The ability of rTcMIP to act as adjuvant was studied in vivo in neonatal mouse immunization models, using acellular diphtheria-tetanus-pertussis-vaccine (DTPa) or ovalbumin, and compared to the classical alum adjuvant. As compared to the latter, rTcMIP increases the IgG antibody response towards several antigens meanwhile skewing antibody production towards the Th-1 dependent IgG2a isotype. The amplitude of the rTcMIP adjuvant effect varied depending on the antigen and the co-presence of alum. rTcMIP did by contrast not increased the IgE response to OVA combined with alum. The discovery of the rTcMIP immunostimulatory effect on neonatal cells opens new possibility for potential use as pro-type 1 adjuvant for neonatal vaccines. This, in turn, may facilitate the development of more efficient vaccines that can be given at birth, reducing infection associated morbidity and mortality which are the highest in the first weeks after birth.